Measuring the Inflation gap of Production Costs for Strategic Crops In Iraq to put alternative price model - AlSadi, Osman H. (Al-Mukhtar Journal of Sciences, 2001)
The aim of this study is to measure the inflation gap some strategic crops in irrigated area and compare it with another competitive crops in year 2000 A.D. Fixed prices with 1980 as abase year, were used to find a better crops combination to obtain both optimum revenue and stability in production level. Prices analysis have showed there is a losses in net income for wheat, barley, corn, sun flower, and cotton. That is the main reason let farmers a void producing there crops. For this reason alternative price modle have developed, which depend on reduce the production costs as well as the prices support. The result of suggested model have shows a good revenue and reduce the gap between production cost and suggested prices, which will provide a security of food and agriculture investment needs in future.